2012
DOI: 10.1161/circheartfailure.111.966242
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction in Patients With Heart Failure With Preserved Versus Reduced Ejection Fraction

Abstract: Background-Prior studies in heart failure (HF) have used the Modification of Diet in Renal Disease (MDRD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(65 citation statements)
references
References 28 publications
2
59
0
4
Order By: Relevance
“…Overall, renal dysfunction is present in 30% to 60% of patients with HFpEF 208, 286, 287. The prevalence of renal dysfunction is greater when defined by estimated glomerular filtration rate (eGFR) <60 mL/min/m 2 and high urinary albumin creatinine ratio than by eGFR alone 288.…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Overall, renal dysfunction is present in 30% to 60% of patients with HFpEF 208, 286, 287. The prevalence of renal dysfunction is greater when defined by estimated glomerular filtration rate (eGFR) <60 mL/min/m 2 and high urinary albumin creatinine ratio than by eGFR alone 288.…”
Section: Comorbid Conditionsmentioning
confidence: 99%
“…Patients were divided into four groups on the basis of their eGFR and BUN values at discharge from the hospital. To define renal insufficiency in the patients with HF, we compared three different formulas for estimating GFR, which were the Japanesemodified eGFR equation: 1943 (serum creatinine 21 (22)(23)(24)(25). Receiver-operating characteristics (ROC) analysis revealed that the Japanese-modified eGFR equation (area under the receiver-operating characteristics curve [AUC] =0.62) performed better for predicting all-cause death after discharge than the simplified MDRD-4 formula (AUC=0.61), whereas the Japanese-modified eGFR equation and the CKD-EPI equation (AUC=0.62) showed similar discrimination in predicting all-cause mortality after discharge.…”
Section: Patients and Definitionsmentioning
confidence: 99%
“…13 It was found that approximately 51-58.5% of HFPEF patients had an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 . 14- 16 In fact, lower admission eGFR is a predictor of all-cause mortality and hospitalizations at 12-22 months of follow-up, even after adjustment for covarieart failure (HF) is a global disease and still on the rise, affecting approximately 2% of the Western population, with prevalence increasing sharply from 1% in 40 year-old individuals to 10% in those over 75 years. 1 Although HF was traditionally labeled as 'pump failure' or reduced left ventricular ejection fraction (LVEF), it has become widely recognized that HF can occur even in patients with relatively normal or preserved EF, a condition called HF with preserved EF (HFPEF).…”
Section: Renal Dysfunctionmentioning
confidence: 99%